Container for high purity chemical composed of polyethylene resin

The development of a high-purity chemical container with a specific polyethylene resin formulation and surface characteristics addresses the issue of contaminant elution, ensuring reduced fine particles and metal impurities, thus enhancing chemical purity and storage stability.

JP2025063751APending Publication Date: 2025-04-16TOSOH CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023173197
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

Existing containers for high-purity chemicals made of polyethylene resin fail to adequately minimize the elution of contaminants such as polyethylene resin eluents and metal impurities, leading to insufficient purity and increased fine particles.

Method used

A high-purity chemical container made of polyethylene resin with a specific area ratio on its inner surface, characterized by a deployment area ratio of less than 1.10, maximum roughness Rz of 10.0 μm or less, and a gloss of 40% or more, which reduces fine particle and metal impurity elution.

Benefits of technology

The container effectively minimizes the elution of fine particles and metal impurities, making it suitable for small containers of 20L or less, and maintaining chemical purity even after long-term storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063751000001
    Figure 2025063751000001
Patent Text Reader

Abstract

To provide a high purity chemical container made of a polyethylene resin which suppresses elution of a pollutant such as an eluted material derived from a polyethylene resin and a degraded substance in its content as much as possible.SOLUTION: A high purity chemical container is composed of a polyethylene resin and has a development area ratio of an inner surface of the container of 1.10 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a high-purity chemical container made of polyethylene resin. [Background technology]

[0002] In recent years, the demand for high-purity chemicals has increased with the remarkable development of the electronics industry. High-purity chemicals are used as essential chemicals for the manufacture of electronic circuits such as large-scale, integrated LSIs. Specifically, sulfuric acid, hydrochloric acid, nitric acid, hydrofluoric acid, ammonium fluoride, hydrogen peroxide, isopropyl alcohol, xylene, TMAH (tetramethylammonium hydroxide), methanol, acetic acid, phosphoric acid, ammonia water, PGMEA (propylene glycol methyl ether acetate), DMSO (dimethyl sulfoxide), NMP (N-methyl-2-pyrrolidone), etc. are used for wafer cleaning and etching, wiring and insulating film etching, jig cleaning, developing solution, resist dilution solution, resist stripping solution, drying, etc. Fluorine-based resins and polyethylene resins are mainly used as container materials for these high-purity chemicals of 20L or less, such as 18L containers, 4L containers, and 1L containers. As the integration density of semiconductor circuits increases, the demand for reducing impurities and particulates in these chemicals becomes more stringent. To satisfy these stringent demands, the cleanliness requirements for the containers in which these chemicals are filled are also increasing year by year.

[0003] One method for solving this problem is to use a specific tetrafluoroethylene copolymer, but the tetrafluoroethylene copolymer has the problem of being expensive (see Patent Document 1). In addition, there have been proposals for containers that suppress the amount of hydrocarbon solvents extracted from polyethylene resins and the content of low molecular weight components, and limit the amount of antioxidants, neutralizing agents, and light stabilizers added as much as possible, but improvements to the effects of ash from catalyst components remaining in the polyethylene resin are insufficient, and measures to reduce the concentration of metal impurities eluted into chemicals are incomplete. Also, the level of fine particles is insufficient at 0.2 μm or more (see Patent Documents 2 and 3).

[0004] In addition, the density is 0.940 to 0.970 g / cm 3 A polyethylene for high-purity chemical containers and a high-purity chemical container have been proposed, which are characterized by a melt flow rate of 2 to 50 g / 10 min at a temperature of 190°C and a load of 21.6 kg, a ratio (Mw / Mn) of weight average molecular weight (Mw) to number average molecular weight (Mn) determined by gel permeation chromatography (GPC) of 8 to 15, and an ash content of 50 PPM or less in the polyethylene resin; however, improvements to the effects of ash due to catalyst components remaining in the polyethylene resin are insufficient, and measures to reduce the concentration of metal impurities eluted into chemicals have not been completed (see Patent Document 4).

[0005] Furthermore, the density is 0.940 to 0.970 g / cm 3 A polyethylene resin for ultra-high purity chemical containers and a high purity chemical container have been proposed, which have the following properties: a melt flow rate of 2 to 8.5 g / 10 min at a temperature of 190°C and a load of 21.6 kg, a ratio (Mw / Mn) of 8 to 15 of weight average molecular weight (Mw) to number average molecular weight (Mn) determined by gel permeation chromatography (GPC), a molecular weight distribution curve obtained using GPC showing that components having a molecular weight of 1000 or less account for 0.30% by weight or less, and an ESCR of 130 hours or more. However, when made into a small container, the surface smoothness was insufficient (see Patent Document 5). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2000 / 17057 [Patent Document 2] Japanese Patent Application Publication No. 7-62161 [Patent Document 3] Japanese Patent Application Publication No. 7-257540 [Patent Document 4] Japanese Patent Application Publication No. 11-80257 [Patent Document 5] Patent No. 6705157 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a high-purity chemical container which minimizes the elution of contaminants such as eluted products and deteriorated products of polyethylene resin. [Means for solving the problem]

[0008] As a result of intensive research to solve the above-mentioned problems, the inventors discovered that a container whose inner surface is made of a polyethylene resin having a specific developed area ratio can be used as a high-purity chemical container with low levels of polyethylene-derived fine particles and metal impurities derived from polymerization catalyst components, and thus developed the present invention.

[0009] That is, the respective aspects of the present invention are [1] to [7] shown below. [1] A high-purity chemical container made of polyethylene resin with an inner surface developed area ratio of 1.10 or less. [2] The high-purity chemical container according to [1] above, wherein the maximum roughness Rz of the container's inner surface is 10.0 μm or less. [3] A container for high-purity chemicals according to any one of the above [1] to [2], wherein the gloss of the inner surface of the container is 40% or more. [4] A container for high-purity chemicals according to any one of [1] to [3] above, in which the number of particles of 0.1 μm or more eluted from the container after filling the container with ultrapure water and storing it at 40°C for 35 days is 10 particles / mL or less. [5] The container for high-purity chemicals according to any one of [1] to [4] above, wherein the polyethylene resin has a melt flow rate (hereinafter, referred to as HLMFR) of 21 to 80 g / 10 min at a temperature of 190°C under a load of 21.6 kg, and a ratio (Mw / Mn) of weight average molecular weight (Mw) to number average molecular weight (Mn) of 5.0 to 7.9 as determined by gel permeation chromatography (GPC). [6] The container for high-purity chemicals according to the above [5], wherein the polyethylene resin is a polyethylene resin having the following properties (1) to (5): (1) Density (JIS K6922-1) is 0.945 to 0.955 g / cm3 (2) Melt flow rate (MFR) at 190°C and a load of 2.16 kg is 0.5 to 1.5 g / 10 min. (3) In the molecular weight distribution curve obtained using GPC, the content of components with a molecular weight of 1,000 or less is 0.30% by weight or less. (4) Metal content is 15 ppm or less for polyethylene resin (5) Environmental stress cracking resistance (ESCR) of 100 hours or more [7] The polyethylene resin has an MFR of 20 to 40 g / 10 min and a density of 0.960 to 0.970 g / cm 3 and an ethylene polymer having an HLMFR of 0.10 to 10 g / 10 min at 190°C and a load of 21.6 kg and a density of 0.920 to 0.940 g / cm 3 and a weight ratio of the two components is 40:60 to 60:40. Effect of the Invention

[0010] According to the present invention, a high-purity chemical container containing less fine particles derived from polyethylene resin and less metal impurities derived from polymerization catalyst components can be provided. In addition, a high-purity chemical container suitable for small containers of 20 L or less in particular, which contains less fine particle components eluted from the filled chemicals and has less fine particle elution even after long-term storage can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The high-purity chemical container according to one embodiment of the present invention is made of polyethylene resin and has an inner surface development area ratio of 1.10 or less, preferably 1.06 or less. If the inner surface development area ratio of the container is 1.06 or less, the amount of fine particles derived from polyethylene resin and metal impurities derived from polymerization catalyst components that dissolve into the high-purity chemical content is reduced, making the container suitable for storing high-purity chemicals. Here, the development area ratio refers to the ratio of surface area to area (surface area / area). If the development area ratio of the container exceeds 1.10, the area in contact with the content liquid of high-purity chemicals increases, and the amount of fine particles derived from polyethylene resin increases, making the container unsuitable as a high-purity chemical container.

[0012] The maximum roughness Rz of the inner surface of a high-purity chemical container is preferably 10.0 μm or less, and more preferably 5.0 μm or less. If Rz is 10.0 μm or less, the molded product will have an excellent appearance. Furthermore, air bubbles in the chemical do not remain in the roughened areas and are not detected as fine particles, so the number of fine particles does not increase. Rz is expressed by calculating the sum of the height of the highest peak and the depth of the deepest valley in the roughness curve over the reference length.

[0013] The gloss of the inner surface of a high-purity chemical container is preferably 40% or more, and more preferably 50% or more, in order to provide a container with a good glossy feel, excellent surface smoothness, and excellent defoaming properties for chemicals.

[0014] Here, high-purity chemicals refer to chemicals with low metal and particulate content that are used in the wafer cleaning and etching processes in semiconductor manufacturing processes. Examples of high-purity chemicals include ultrapure water, hydrogen peroxide, sulfuric acid, nitric acid, hydrochloric acid, hydrofluoric acid, ammonia water, CMP slurry, and photoresist liquid.

[0015] The high-purity chemical container has an inner surface area of ​​5000 cm 2 It is suitable for use in the following small containers, such as containers with a capacity of 10 mL to 20 L.

[0016] The shape of the container may be any shape as long as it is capable of containing and storing high purity chemicals, and examples of the shape include cylindrical and box-shaped containers.

[0017] The container may be a single-layer container made of polyethylene resin alone, a multi-layer container made of different polyethylene resins laminated together, or a multi-layer container made of polyethylene resin laminated together with a resin other than polyethylene resin. For example, in order to reinforce the barrier properties for high-purity chemicals and the strength of the container, the container may be a multi-layer container in which an inner layer is made of polyethylene resin, an intermediate layer is made of one or more resins selected from ethylene-vinyl alcohol copolymer, polyvinyl alcohol resin, polyamide resin, and recycled polyethylene resin, and an outer layer is reinforced with polyethylene resin or FRP or the like having drop impact resistance.

[0018] Furthermore, since the high-purity chemical container is a preferred container for storing and storing high-purity chemicals, it is preferred that the number of particles of 0.1 μm or more eluted from the container when the container is filled with ultrapure water and stored at 40° C. for 35 days is 10 particles / mL or less. If the number of particles of 0.1 μm or more is 10 particles / mL or less, the container can accommodate the miniaturization of LSIs.

[0019] Since the high-purity polyethylene resin for pharmaceutical containers has excellent moldability and excellent surface smoothness when made into a container, the HLMFR (JIS K6922-1) is preferably 21 to 80 g / 10 min, and more preferably 30 to 60 g / 10 min.

[0020] In addition, since the polyethylene resin for high-purity chemical containers has excellent chemical resistance and excellent surface smoothness when made into a container, the ratio Mw / Mn of Mw to Mn determined by GPC is preferably 5.0 to 7.9, and more preferably 6.0 to 7.7.

[0021] High-purity polyethylene resin for chemical containers has a density (JIS K6922-1) of 0.945 to 0.955 g / cm because it produces containers with excellent chemical resistance and a particularly small number of fine particles. 3 and more preferably 0.947 to 0.952 g / cm 3 It is.

[0022] High-purity polyethylene resins for pharmaceutical containers have excellent moldability and excellent surface smoothness when made into containers, and therefore their MFR (JIS K6922-1) at 190°C and a load of 2.16 kg is preferably 0.5 to 1.5 g / 10 min, and more preferably 0.8 to 1.2 g / 10 min.

[0023] Since high-purity polyethylene resin for pharmaceutical containers produces containers with a particularly small number of fine particles, the molecular weight distribution curve obtained using GPC preferably contains 0.30% by weight or less of components with a molecular weight of 1000 or less, and more preferably 0.25% by weight or less.

[0024] Since polyethylene resin for high-purity pharmaceutical containers is a container that elutes little metal from the container, the metal content is preferably 15 PPM or less relative to the polyethylene resin, and more preferably 10 PPM. The metal content is the ratio of metal to the total resin in weight ppm, and is obtained by incinerating the resin and then melting it with alkali, and refers to the remaining Mg, Al, Ti, etc.

[0025] Since the polyethylene resin for high-purity chemical containers provides containers with particularly excellent chemical resistance, it is preferable that the ESCR is 100 hours or more.

[0026] The polyethylene resin for high-purity pharmaceutical containers can be produced by a highly active catalyst such as a Ziegler catalyst or a metallocene catalyst. For example, the polyethylene resin can be suitably produced by using a highly active Ziegler catalyst consisting of a transition metal compound such as titanium or zirconium, a magnesium compound, and an organoaluminum compound as a polymerization catalyst, and copolymerizing ethylene or ethylene and an α-olefin having 3 to 20 carbon atoms in a ratio that gives a desired density.

[0027] The catalyst may be one described in Japanese Patent No. 3319051.

[0028] Examples of the α-olefin having 3 to 20 carbon atoms include propylene, 1-butene, 4-methyl-1-pentene, 3-methyl-1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicosene.

[0029] The polymerization method for producing polyethylene resin for high-purity pharmaceutical containers is slurry polymerization using a polymerization solvent having a carbon number of 6 to 10, such as normal hexane or normal heptane, in order to keep the concentration of metal impurities eluted in the pharmaceutical low and to limit the incorporation of low-molecular weight polymers that cause the generation of fine particles into the resin. The polymerization solvent has an MFR of 20 to 40 g / 10 min and a density of 0.960 to 0.970 g / cm. 3 and a low molecular weight ethylene polymer having an HLMFR of 0.1 to 10 g / 10 min and a density of 0.920 to 0.940 g / cm 3 and a weight ratio of the two components is preferably 40:60 to 60:40. The two components, the low molecular weight component and the high molecular weight component, can be produced, for example, by a two-stage polymerization method.

[0030] Furthermore, since the polyethylene resin for high-purity pharmaceutical containers will result in containers with little metal contaminants, it is preferable that it does not contain any additives such as antioxidants, light resistance stabilizers, and neutralizing agents.

[0031] High-purity drug containers can be obtained by using polyethylene resins having specific properties and molding them into container shapes by direct blow molding, injection molding, injection blow molding, etc. In particular, a blow molding method using a direct blow molding machine installed in a clean room and using air from which fine particles have been removed by a filter as the blow air makes it possible to manufacture clean containers. EXAMPLES

[0032] The present invention will be described below with reference to examples, but is not limited to these examples. The test methods used in the examples and comparative examples are as follows.

[0033] (1) Ratio of the deployed area of ​​the container's inner surface Containers with an internal volume of 800 mL or 500 mL obtained by blow molding polyethylene resin were used. The surface area and area of ​​the inner surface of the container body were measured using a shape measuring laser microscope (Keyence Corporation, VK-X200), and the developed area ratio (surface area / area) was calculated.

[0034] (2) Maximum roughness of the container inner surface Rz The maximum roughness Rz value of the inner surface of the container body was measured using a shape measuring laser microscope (Keyence Corporation, VK-X200).

[0035] (3) Gloss of the inner surface of the container The gloss of the inner surface of the container body at an incident angle of 60° was measured using a variable angle glossmeter (300A, manufactured by NIPPON DENSYOKU).

[0036] (4) Number of fine particles In a clean room at 23°C, an unwashed container was filled with ultrapure water to 80% of its internal volume, the container was capped and shaken 15 times, and then left to stand for 35 days in a clean oven (Yamato Scientific Co., Ltd., DE411) set at 40°C. The number of particles of 0.1 μm or more in the filled water was then measured using a particle counter (Rion Co., Ltd., controller: KE-40B1, particle sensor: KS-42A). The number of particles in the water is expressed in particles / mL.

[0037] (5) HLMFR The measurement was performed in accordance with JIS K6922-1 at 190°C and a load of 21.6 kg.

[0038] (6) Mw / Mn The molecular weight was measured by GPC using Tosoh HLC-8321GPC / HT (columns: Tosoh TSKgel guardcolumn HHR and TSKgel GMHHR-H) and 1,2,4-trichlorobenzene as the eluent. The molecular weight calibration curve was calibrated using polystyrene samples with known molecular weights.

[0039] (7) Density The measurement was performed by the density gradient tube method in accordance with JIS K6922-1.

[0040] (8)MFR The measurement was performed in accordance with JIS K6922-1 at 190°C and a load of 2.16 kg.

[0041] (9) Components with molecular weight of 1,000 or less The ratio of the integral amount of components having a molecular weight of 1000 or less was calculated from the molecular weight distribution curve obtained by GPC measurement.

[0042] (10)Amount of metals contained The polyethylene resin was incinerated and then fused with an alkali to produce a solution, which was used as the measurement solution. The amount of metal contained in the sample was measured by ICP-AES measurement using an Optima 8300.

[0043] (11) Environmental Stress Cracking Resistance (ESCR) In accordance with JIS K6922-2, the test piece was immersed in a nonionic surfactant (10 wt% aqueous solution) at 50°C, and the time it took for the test piece to break with a 50% probability (F50 value) was measured.

[0044] (12) Blow molding Using a direct blow molding machine MSE-50E / 54M-A (manufactured by Tahara Co., Ltd.) with a 50 mm diameter extrusion screw, the parison was continuously extruded from the tip of the die at a cylinder temperature of 190 to 200 °C and a screw rotation speed of 10 to 18 revolutions, resulting in an average wall thickness of 1 mm and an internal volume of 800 mL (internal area = 560 cm). 2 ) or 500mL (internal area = 420cm 2 ) containers were molded.

[0045] Example 1 Preparation of Solid Catalyst Component In a 3L glass flask equipped with a stirrer, 30.0g (1.23mol) of metallic magnesium powder and 168.0g (0.494mol) of titanium tetrabutoxide were placed, and 192g (2.59mol) of n-butanol in which 1.5g of iodine had been dissolved was added over a period of 2 hours at 90°C. The mixture was then stirred for 2 hours at 140°C under a nitrogen seal while removing the hydrogen gas that was generated. After this was brought to 110°C, 26g (0.125mol) of tetraethoxysilane and 19g (0.125mol) of tetramethoxysilane were added, and the mixture was further stirred for 2 hours at 140°C. Next, 2.1 liters of hexane was added to obtain a homogeneous solution.

[0046] This homogeneous solution was placed in a 10L stainless steel autoclave equipped with a stirrer, and the internal temperature of the autoclave was kept at 45°C. 800mL of a hexane solution containing 1.0mol of diethylaluminum chloride and 0.5mol of i-butylaluminum dichloride was added over 1 hour, and the mixture was stirred at 60°C for 1 hour to generate particles. After the temperature was returned to 45°C, 1.04kg (3.35mol) of a 50% hexane solution was added over 2 hours. After all the contents were added, the mixture was stirred at 60°C for 1 hour to obtain a solid catalyst component. The obtained solid catalyst component was used to remove remaining unreacted materials and by-products using hexane, and then used as a hexane slurry for the production of polyethylene resin.

[0047] <Production of Polyethylene A> The reactor was operated at a temperature of 85°C and a total pressure of 30 kg / cm while feeding 110 L / hr of dehydrated and purified hexane, 110 mmol of tributylaluminum as an organoaluminum compound, 0.4 g / hr of a solid catalyst component, 25.4 kg / hr of ethylene, and 0.45 mol / mol of hydrogen to the first stage of a 370 L continuous polymerization reactor. 2 The first stage of ethylene polymerization (low molecular weight fraction) was carried out continuously under the conditions of an average residence time of 3.4 hours. The MFR of the low molecular weight fraction was 35 g / 10 min and the density was 0.968 g / cm. 3 It was.

[0048] The hexane slurry containing the first-stage polymer was subjected to removal of unreacted hydrogen and ethylene in a flash tank, and then introduced into a second-stage polymerization reactor having an internal volume of 545 L. While additional hexane was supplied to this polymerization reactor at 45 L / hr, ethylene was supplied at 21.5 kg / hr, 1-butene at 1.9 kg / hr, and hydrogen at a concentration relative to ethylene of 0.016 mol / mol, respectively, and the polymerization was continued at a temperature of 80° C. and a total pressure of 20 kPa / cm. 2 Ethylene polymerization (high molecular weight fraction) was carried out under the conditions of an average residence time of 3.3 hours. The HLMFR of the high molecular weight fraction was 2.2 g / 10 min and the density was 0.930 g / cm 3The discharge from the second-stage polymerization reactor was passed through a flash tank to remove unreacted hydrogen, ethylene, and 1-butene, and was then washed with 50 L / hour of hexane before being dried to obtain a powder mixture of ethylene-based copolymers. The proportion of low molecular weight components was 55% by weight, and the proportion of high molecular weight components was 45% by weight. The powder polymerized in two stages in the above manufacturing process was pelletized without the addition of any additives, to obtain polyethylene A. The results of the physical property measurements are shown in Table 1.

[0049] Polyethylene A was used to mold an 800 mL container, and the developed area ratio, maximum roughness Rz, gloss, and number of fine particles on the inner surface of the container were measured using the container. The results are shown in Table 1.

[0050] Example 2 The same polyethylene A as in Example 1 was used to mold a 500 mL container, and the developed area ratio, maximum roughness Rz, gloss, and number of fine particles on the inner surface of the container were measured using the resulting container. The results are shown in Table 1.

[0051] Example 3 <Production of Polyethylene B> Ethylene and butene-1 were copolymerized in hexane in the same manner as in Example 1, except that hydrogen was supplied to the first-stage polymerization reactor at a concentration ratio to ethylene of 0.40 mol / mol, and 1-butene was supplied to the second-stage polymerization reactor at 2.5 kg / hr and hydrogen was supplied to the second-stage polymerization reactor at a concentration ratio to ethylene of 0.020 mol / mol. Polymer powder was obtained by a two-stage polymerization method. The MFR of the low molecular weight component in the first-stage polymerization reactor was 27 g / 10 min, and the density was 0.967 g / cm. 3 The HLMFR of the high molecular weight component in the second stage polymerization reactor was 3.2 g / 10 min, and the density was 0.928 g / cm 3 The powder obtained by the two-stage polymerization was pelletized without adding any additives to obtain polyethylene B. The results of the measurement of the physical properties are shown in Table 1.

[0052] Polyethylene B was used to mold an 800 mL container, and the developed area ratio, maximum roughness Rz, gloss, and number of fine particles on the inner surface of the container were measured using the resulting container. The results are shown in Table 1.

[0053] Comparative Example 1 <Production of Polyethylene C> Ethylene and butene-1 were copolymerized in hexane in the same manner as in Example 1, to obtain a polymerized powder by a two-stage polymerization method, except that hydrogen was supplied to the first-stage polymerization reactor at a concentration ratio to ethylene of 0.25 mol / mol and hydrogen was supplied to the second-stage polymerization reactor at a concentration ratio to ethylene of 0.050 mol / mol. The MFR of the low molecular weight component in the first stage polymerization reactor was 18 g / 10 min, and the density was 0.967 g / cm 3 The HLMFR of the high molecular weight component in the second stage polymerization reactor was 8.5 g / 10 min, and the density was 0.932 g / cm 3 The powder obtained by the two-stage polymerization was pelletized without adding any additives to obtain polyethylene C. The results of the measurement of the physical properties are shown in Table 1.

[0054] Polyethylene C was used to mold an 800 mL container, and the developed area ratio, maximum roughness Rz, gloss, and number of fine particles on the inner surface of the container were measured using the container. The results are shown in Table 1. Comparative Example 2 <Production of Polyethylene D> Ethylene and butene-1 were copolymerized in hexane in the same manner as in Example 1, to obtain a polymerized powder by a two-stage polymerization method, except that hydrogen was supplied to the first-stage polymerization reactor at a concentration ratio to ethylene of 0.70 mol / mol and hydrogen was supplied to the second-stage polymerization reactor at a concentration ratio to ethylene of 0.010 mol / mol.

[0055] The MFR of the low molecular weight component in the first stage polymerization reactor was 50 g / 10 min, and the density was 0.969 g / cm 3 The HLMFR of the high molecular weight component in the second stage polymerization reactor was 1.4 g / 10 min, and the density was 0.927 g / cm 3 The powder obtained by the two-stage polymerization was pelletized without adding any additives to obtain polyethylene D. The results of the measurement of the physical properties are shown in Table 1.

[0056] Polyethylene D was used to mold an 800 mL container, and the above-mentioned evaluation of the container's inner surface and measurement of fine particles were carried out using the resulting container. The results are shown in Table 1.

[0057] Comparative Example 3 The same polyethylene D as in Comparative Example 2 was used to mold a 500 mL container, and the above-mentioned developed area ratio, maximum roughness Rz, gloss, and number of fine particles were measured using the resulting container. The results are shown in Table 1.

[0058] Comparative Example 4 As polyethylene E, the following commercially available high-density polyethylene was used.

[0059] Tosoh Corporation, (product name) Nipolon Hard 8022 (MFR = 0.35 g / 10 min, density = 0.958 g / cm 3 , no additives added) An 800 mL container was molded using polyethylene E, and the above-mentioned evaluation of the container's inner surface and measurement of the number of fine particles were carried out. The evaluation results of the resin's physical properties and the container are shown in Table 1.

[0060] Comparative Example 5 As polyethylene F, the following commercially available high-density polyethylene was used.

[0061] Tosoh Corporation, (product name) Nipolon Hard 8D01A (MFR = 0.05 g / 10 min, density = 0.957 g / cm 3 , no additives added) Polyethylene F was used to mold an 800 mL container, and the developed area ratio, maximum roughness Rz, gloss, and number of fine particles on the inner surface of the container were measured. The evaluation results of the resin properties and the container are shown in Table 1.

[0062] [Table 1]

Claims

1. A high-purity chemical container made of polyethylene resin, the container having an inner surface development area ratio of 1.10 or less.

2. 2. The high purity chemical container according to claim 1, wherein the maximum roughness Rz of the container inner surface is 10.0 μm or less.

3. 2. The container for high purity chemicals according to claim 1, wherein the gloss of the inner surface of the container is 40% or more.

4. 2. The high-purity chemical container according to claim 1, wherein the number of particles of 0.1 μm or more eluted from the container after filling the unwashed container with ultrapure water and storing the container at 40° C. for 35 days is 10 particles / mL or less.

5. The container for high-purity chemicals according to claim 1, wherein the polyethylene resin has a melt flow rate (hereinafter, referred to as HLMFR) of 21 to 80 g / 10 min at a temperature of 190° C. and a load of 21.6 kg, and a ratio (Mw / Mn) of weight average molecular weight (Mw) to number average molecular weight (Mn) of 5.0 to 7.9 as determined by gel permeation chromatography (GPC).

6. The container for high-purity chemicals according to claim 5, wherein the polyethylene resin has the following properties (1) to (5). (1) Density (JIS K6922-1) is 0.945 to 0.955 g / cm 3 (2) Melt flow rate (hereinafter, MFR) at 190°C and a load of 2.16 kg is 0.5 to 1.5 g / 10 min. (3) In the molecular weight distribution curve obtained by GPC, the content of components having a molecular weight of 1,000 or less is 0.30% by weight or less. (4) Metal content is 15 ppm or less for polyethylene resin (5) Environmental stress cracking resistance (ESCR) of 100 hours or more

7. The polyethylene resin has an MFR of 20 to 40 g / 10 min and a density of 0.960 to 0.970 g / cm 3 and an ethylene-based polymer having an HLMFR of 0.10 to 10 g / 10 min and a density of 0.920 to 0.940 g / cm 3 6. The high purity chemical container according to claim 5, comprising two components, an ethylene polymer represented by the formula:

Citation Information

Patent Citations

  • Polyolefin for container for aqueous hydrogen peroxide solution

    JP1995062161A

  • Container for high-purity solvent

    JP1995257540A

  • Polyethylene resin for highly pure reagent container and highly pure reagent container comprising same

    JP1999080257A

  • Polyethylene resin for ultra-high purity chemical containers and high purity chemical containers made therefrom

    JP6705157B2

  • Blow-molded container

    WO2000017057A1